Frequency of Amblyopia in Uncorrected an Isometropia in Children of age between 5-10 years - Tahir Mahmood Khan, Shahid Anwar Bhatti, Abdul Haleem, Anwar ul Haq, Syed Naveed Haider, Muhammad Shamim Ul Hunsain, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Uncorrected anisometropia is a leading cause of amblyopia and preventable visual impairment in children. Anisometropia disrupts binocular vision, resulting in cortical suppression and reduced visual acuity in the affected eye. Early identification and treatment are crucial to prevent permanent vision loss. However, the lack of routine vision screening in Pakistan often delays diagnosis and treatment. Objectives: This study aimed to determine the prevalence of amblyopia among Pakistani children aged 5–10 years with uncorrected anisometropia and to evaluate the relationship between anisometropia severity and amblyopia. Methods: A cross-sectional, hospital-based study was conducted at multiple ophthalmology centres in Pakistan from January 2020 to December 2022. A total of 150 children with uncorrected anisometropia underwent comprehensive assessments, including best-corrected visual acuity, cycloplegic refraction, and ocular alignment tests. Amblyopia was defined as BCVA ≤ 20/40 in one eye or an interocular difference of ≥2 lines. Data were analyzed using SPSS version 25.0, and chi-square tests were applied to evaluate the association between anisometropia severity and amblyopia. Results: Amblyopia was diagnosed in 32% of the study population. The prevalence increased with anisometropia severity: 13.3% in mild cases, 29.1% in moderate cases, and 68.6% in severe cases (p<0.001). The mean age of amblyopia diagnosis was 7.5 ± 1.3 years. No significant gender difference in prevalence was found (p=0.69). Conclusion: Uncorrected anisometropia significantly increases amblyopia risk. Early detection and timely treatment are essential to prevent long-term visual impairment. Implementing school vision screenings and improving access to refractive correction services could substantially reduce childhood amblyopia in Pakistan. Keywords: Amblyopia, Anisometropia, Childhood Visual Impairment, Pediatric Ophthalmology, Vision Screening, Pakistan.